Understanding the Preference and Course Experience of online Management courses among Gen Y students - Nalini, Palaniswamy; Subhashree, Sundarraj (Journal of Contemporary Research in Management (JCRM), 2017)
Management education is finding a visible amount of disruptive innovation in the early 70s and late 20s. All this change is very visible from mid of 70â€™s after the technology human interface development. The growing technology, lifestyle changes and mobility have given way for new innovations in education. In Mid of 1970â€™s e-mail and computer conferencing have adopted by educators and adapters by educational environments that radically altered the relationship of the learner to the teacher and the content of the curriculum. Traditional behaviour like geographies have been replaced in an unpredictable way by new form massive online open courses (MOOC) Harasim, L. (1996). An online course should beÂ engaging,Â soÂ thatÂ theÂ learnerÂ enjoysÂ theÂ learningÂ andÂ isÂ ableÂ toÂ notÂ onlyÂ assimilateÂ it,Â butÂ retainÂ it and apply it.â€ Itâ€™s a directed learning process, comprised of educational information (articles, videos, images, web links), communication (messaging, discussion forums) and some way to measure studentsâ€™ achievement. (Jennifer Berghage 2014),Â TheÂ growingÂ onlineÂ educationÂ hasÂ alsoÂ hadÂ its impact in the ways the subjects are thought Many foreign university is getting the studentsâ€™ attention to take up their courses. This is seen has opportunity has well a threat for many disciplines. In particular, to Management education always student wants to benchmark themselves to the western universities. A serious scenario in the last decade, many management institutions failed to redesign their courses and also benchmark themselves to the world class management education.